Morphological Growth of Soybean (Glycine max L.) Treated with Soil Application of Humic Acid under Different Cultivation Periods - Chnar Hama Noori Meerza; Shara Salih Ali (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2023)
The demand of organic cultivation of plants is increasing and soil application of organic fertilizer reduces the hazardous usage of inorganic fertilizer and Humic acid is an organic compound derived from plant and animal residues and microbial cells with long-term physical, chemical, and biological processes. In addition, ultivation of soybean in Kurdistan region is not in a wide value therefore, the objective of this study was to determine the impact of soil application of different rates of Humic acid as an organic fertilizer on the growth characteristic of soybean cultivated and determining the best cultivation period for soybean growth. The experiment was conducted in randomized complete block design with two factor treatments and 3 replication, the first factor was one dose soil application of four different Humic Acid rates (HAR) which were (0 (control), 2,4,6,8 g/L) and two cultivation period (CP) which were cultivation Period 1 (CP1) on 15 May 2022 and cultivation Period 2 (CP2) on 1st of June 2022. Observations were made against the growth parameters of plant height number of branches, leaf area, root length, shoot fresh weight and shoot dry weight. The effect of soil application of humic acid rates (HAR) was highly significant on the plant height and root length and significant on the No. of branches, shoot fresh and dry weight. While, cultivation period insignificantly affected the growth parameter except for leaf area. was significant. The maximum plant height, number of branches, leaf area, root length, shoot fresh and dry weight were observed with soil application of 8 g/L of humic acid which were (82.83 (cm), 23.33, 8815 (mm2), 68.83 (cm), 503.33 (g) and 190.00 (g) respectively. The highest plant height (72 cm), number of branches (18.87), leaf area (7714 mm2), root length (57.13 g), shoot fresh (263.67 g) and dry weight (102.93 g) were observed when the planted cultivated in 1st period (CP1) compared to CP2.